2016
DOI: 10.19104/jghd.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors for Giardiasis among Children in District Anantnag of Kashmir Valley, India

Abstract: The present study aims to determine the prevalence of giardiasis among different age groups, sexes and rural/urban categories of children in district Anantnag of Kashmir valley and to find out the risk factors associated with it. A total of 268 samples were collected out of which 8.2% were found to be positive for giardiasis. The prevalence rate was significantly higher in case of male children (10.4%) than in females (6.29%). The prevalence rate was highest in the age group of 5-8 years (13.7%) and least in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
2
1
Order By: Relevance
“…lamblia infection than counterparts ( Table 4 ). This is in consistent with the study from India ( P = 0.01) [ 40 ] and in Tirana [ 41 ]. Another study reported in Brazil stated that the age group of 5–10 had 1.18 (AOR = 1.18, 90% CI; 1.0–1.36; P = 0.002) times more likely infected with G .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…lamblia infection than counterparts ( Table 4 ). This is in consistent with the study from India ( P = 0.01) [ 40 ] and in Tirana [ 41 ]. Another study reported in Brazil stated that the age group of 5–10 had 1.18 (AOR = 1.18, 90% CI; 1.0–1.36; P = 0.002) times more likely infected with G .…”
Section: Discussionsupporting
confidence: 93%
“…lamblia were higher among the school children belonging to rural areas such as Aregeda primary school being 45.8% than that of urban areas in Hantate elementary school 12.4%. This finding is consistent with a study conducted in India which stated that, the infection rate was higher among the children belonging to rural areas (9.87%) than in children belonging to urban areas being 6.03% [ 40 ]. As the present study showed that, rural primary schools in Aregeda had 9.97 (AOR = 9.979, 95% CI; 1.976–15.392, P = 0.005) times more likely to be exposed with G .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Sikkim of India, a prospective study among symptomatic children (<15 years) was done where Giardia cysts were found in 5% of cases by wet mount [99]. About 8.2% of patients were positive for giardiasis through the direct smear method in Kashmir Valley, India [100]. Another study in Lucknow of India showed that Giardia was detected 15.5% by immediate wet mount preparation [101], much higher than the current study findings.…”
Section: Discussioncontrasting
confidence: 70%
“…In Sikkim, India, a prospective study among symptomatic children (<15 years) was done where Giardia cysts were found in 5% of cases by wet mount [ 109 ]. About 8.2% of patients were positive for giardiasis through the direct smear method in Kashmir Valley, India [ 110 ]. Another study in Lucknow, India, showed that Giardia was detected in 15.5% by immediate wet mount preparation [ 111 ], much higher than the current study findings.…”
Section: Discussionmentioning
confidence: 99%